Recenzja edycji: Jan Kochanowski, Carmina latina, cz. 3: Komentarz, oprac. Z. Głombiowska, Wydawnictwo Uniwersytetu Gdańskiego, Gdańsk 2013, ss. 983 - Płachcińska, Krystyna (Collectanea Philologica, 2014)
The third part of the critical edition of Jan Kochanowski’s corpus in Latin, published by Zofia Głombiowska in 2013, contains an editorial commentary. This volume is the last part of a large and impressive work which was necessary for the academic knowledge of Polish Renaissance literature.